Comparative study utilizing different post-breeding treatment regimens in cyclic Arabian mares - Khalid Mohammed Karam (Veterinary World, 2021)
Background and Aim: Post-breeding treatment is the most common practice in the reproductive management of mares. Oxytocin, uterine lavage, and intrauterine (I/U) antibiotic are usually used as prophylactic therapy. This study aimed to determine the most efficient prophylactic treatment regimen among six treatment protocols applied during natural breeding of cyclic Arabian mares.